Social Education Management of Cultural Tourism Objects Post Covid-19 in Aceh Province, Indonesia - Rahmi Novalita, Rahmi Novalita; Wahyuni, Sri; Sumanti, Sumanti; Ali, Muhammad (Sumatra Journal of Disaster, Geography and Geography Education, 2024)
This study aims to describe about; 1) the implementation of the social education model for managing cultural tourism objects after Covid 19, 2) the effectiveness of the social education model for managing cultural tourism objects after Covid 19 using the tourism awareness education module. This type of research is Research and Development (R&D) research using the ADDIE model. The subject of the development is the community as a tourism-aware group of the Makam Syuhada Lapan amounting to 20 people. The sampling technique used incidental sampling. The results showed that; 1) implementation of the social education model for managing cultural tourism objects through the following stages: a) prospective participants, b) selection of prospective participants, c) socialization of the introduction of tourism awareness learning programs using modules, d) implementation of tourism awareness learning programs, e) mentoring. 2) The effectiveness of social education in managing cultural tourism objects using modules is considered effective in terms of improving learning outcomes in group 1 and group 2. This proves that social education has been effective in providing awareness to the public in managing cultural tourism objects